Influence of the Homopolar Dihydrogen Bonding CH⋅⋅⋅HC on Coordination Geometry: Experimental and Theoretical Studies. Issue 46 (1st October 2015) - Safin, Damir A.; Babashkina, Maria G.; Robeyns, Koen; Mitoraj, Mariusz P.; Kubisiak, Piotr; Garcia, Yann
Abstract: The reaction of the N‐thiophosphorylated thiourea (HOCH2 )(Me)2 CNHC(S)NHP(S)(O i Pr)2 (HL), deprotonated by the thiophosphorylamide group, with NiCl2 leads to green needles of the pseudotetrahedral complex [Ni(L‐1, 5‐ S, S′ )2 ]⋅ 0.5 ( n ‐C6 H14 ) or pale green blocks of the trans square‐planar complex trans ‐[Ni(L‐1, 5‐ S, S′ )2 ]. The former complex is stabilized by homopolar dihydrogen CH⋅⋅⋅HC interactions formed by n ‐hexane solvent molecules with the [Ni(L‐1, 5‐ S, S′ )2 ] unit. Furthermore, the dispersion‐dominated CH⋅⋅⋅ HC interactions are, together with other noncovalent interactions (CH⋅⋅⋅N, CH⋅⋅⋅Ni, CH⋅⋅⋅S), responsible for pseudotetrahedral coordination around the Ni II center in [Ni(L ‐1, 5‐ S, S′ )2 ]⋅ 0.5 ( n ‐C6 H14 ). Abstract : Hidden attraction : Dispersion‐dominated homopolar CH⋅⋅⋅HC interactions not only stabilize the crystal structures of pseudotetrahedral Ni II units interacting with n ‐hexane molecules, but can also facilitate crystallization (see figure). In addition, they are also responsible, together with other noncovalent interactions (CH⋅⋅⋅N, CH⋅⋅⋅Ni, CH⋅⋅⋅S), for deviation from planarity around the metal center.